SOME FACTORS AFFECTING INTENTIONAL INJURY IN STUDENTS AT SECONDARY SCHOOLS IN HA NOI (Vietnam Journal of Community Medicine, 2022)
Objectives: To describe some epidemiological features of intentional injury in secondary schoolstudents in Ha Noi.Subjects and methodology: A cross-sectional study was conducted on 1.118 students at twosecondary schools in Hanoi in 2016.Results: Factors affecting intentional injury included demographic features, emotional disorder,behavioral disorder, peer relationship, drug use, bullying and being bullied, and so on.Conclusion: Intentional injury in secondary school studentsise is affected by demographic features,some psychological disorders, drug use, bullying, and being bullied.
Keywords: Intentional injury, emotional disorder, bullying, and being bullied.